FUNGSI DEBIT JENIUS SEBAGAI SALAH SATU INSTRUMEN GERBANG PEMBAYARAN NASIONAL (GPN) - Fadriansyah Nanda Thaimiyah (2021)
In an increasingly modern era and has entered the era of digitalization, people are required to be able to keep up with technological developments. Where now the public can conduct banking transactions through the grip of a smartphone where in the past banking transaction activities could only be carried out directly through the related bank branch offices. Jenius, one of the digital banks in Indonesia issued by Bank BTPN as well as the pioneer or originator of digital banks in Indonesia, was officially launched by BTPN in 2016. This digital banking application from BTPN with the tagline "Experience Banking Reinvented" has succeeded in attracting the attention of the public, especially young people who are known to have high mobility. Jenius assists the public in managing their finances through their smartphone. Jenius also functions as one of the National Payment Gateway (NPG) instruments. The author aims to analyze what are the functions of the Jenius debit in becoming one of the instruments in the National Payment Gateway (NPG)